Ionic fluid as a novel cleaning agent for the control of irreversible fouling in reverse osmosis membrane processes. (1st October 2022) - Choi, Seung-Ju; Kim, Sangsik; Im, Sung-Ju; Jang, Am; Hwang, Dong Soo; Kang, Seoktae
Highlights: Ionic fluid (IF) was firstly applied as cleaning agent on the RO membrane fouling. Mixture of IF and NaOH exhibited the enhanced control of irreversible fouling. Fouling layer became swelled and removed by the intrusion of IF solution. Swelling was induced as pre-existing interactions foulants were weakened by IF. Abstract: While a variety of chemical cleaning strategies has been studied to control fouling in membrane-based water treatment processes, the removal of irreversible foulants strongly bound on membrane surfaces has not been successful. In this study, we firstly investigated the diluted aqueous solutions of ionic fluid (IF, 1-ethyl-3-methylimidazolium acetate) as a cleaning agent for three model organic foulants (humic acid, HA; bovine serum albumin, BSA; sodium alginate, SA). The real-time monitoring of cleaning progress by optical coherence tomography (OCT) showed that fouling layer was dramatically swelled by introducing IF solution and removed by shear force exerted during cleaning. This phenomenon was induced due to the pre-existing interactions between organic foulants were weakened by the intrusion of IF into the fouling layer, which was analyzed by the measurement of adhesion forces using atomic force microscopy (AFM). In the experiments with model foulants and wastewater effluent, IF was added to alkaline cleaning agents (NaOH) to verify the applicability to be supplemented in commercial cleaning agents, and resulted in the significantly enhanced control of irreversible membrane fouling. Implication of utilizing recyclable IF with negligible volatility is that environmental effects of membrane cleaning solutions could be minimized by decreasing usage of cleaning chemicals, while increasing the cleaning efficiency. Graphical abstract: Image, graphical abstract